2006
DOI: 10.1172/jci26620
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin-dependent protein kinase II regulates cardiac Na+ channels

Abstract: In heart failure (HF), Ca 2+ /calmodulin kinase II (CaMKII) expression is increased. Altered Na + channel gating is linked to and may promote ventricular tachyarrhythmias (VTs) in HF. Calmodulin regulates Na + channel gating, in part perhaps via CaMKII. We investigated effects of adenovirus-mediated (acute) and Tg (chronic) overexpression of cytosolic CaMKIIδ C on Na + current (I Na ) in rabbit and mouse ventricular myocytes, respectively (in whole-cell patch clamp). Both acute and chronic CaMKIIδ C overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
560
1
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 483 publications
(616 citation statements)
references
References 43 publications
45
560
1
10
Order By: Relevance
“…In particular, CAMKII‐dependent phosphorylation of Nav1.5 alters I Na gating by reducing current availability at higher pacing rates 27. Moreover, transgenic overexpression of CAMKIIδ promotes QRS prolongation and increases predisposition for VT/VF 27. Indeed, phosphoactive CAMKII levels were markedly upregulated in our porcine MI model in agreement with previous results in human and canine models of ischemic heart failure 32.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In particular, CAMKII‐dependent phosphorylation of Nav1.5 alters I Na gating by reducing current availability at higher pacing rates 27. Moreover, transgenic overexpression of CAMKIIδ promotes QRS prolongation and increases predisposition for VT/VF 27. Indeed, phosphoactive CAMKII levels were markedly upregulated in our porcine MI model in agreement with previous results in human and canine models of ischemic heart failure 32.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we surmised that the differences in the rate dependence of myocardial conduction and excitability are likely related to differences in Na channel activity rather than expression. In recent years, studies have focused on the intricate regulation of Nav1.5 activity by CaMKII,24, 25, 26, 27 a key calcium‐dependent kinase that is activated in MI. In particular, CAMKII activation was shown to modulate Na channel recovery from inactivation 27.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of evidence has demonstrated that CaMKII can also be activated by ROS 21, 22, 23, 24. Once activated, CaMKII can phosphorylate a wide range of key Ca 2+ and Na + regulatory proteins such as LCCs,25, 26, 27, 28 RyRs,29, 30, 31, 32, 33, 34, 35 phosphalamban,29, 34, 36 and Na + channels 37, 38. Importantly, Xie et al39 showed that H 2 O 2 perfusion–induced oxidative CaMKII activation leads to afterdepolarizations in isolated rabbit cardiomyocytes, likely by phosphorylation of Na + channels and LCCs.…”
Section: Introductionmentioning
confidence: 99%